Prevalence and factors associated with double and triple burden of malnutrition among mothers and children in Nepal: evidence from 2016 Nepal demographic and health survey - Dev Ram Sunuwar; Devendra Raj Singh; Pranil Man Singh Pradhan (BMC, 2020)
Abstract Background Malnutrition in mothers and children is a significant public health challenge in developing countries such as Nepal. Although undernutrition in children has been gradually decreasing, the coexistence of various forms of malnutrition in mothers and children has continued to rise globally. There is a gap in knowledge of the coexistence of such multiple burdens of malnutrition in the Nepalese context. The aims of this study were to explore the coexistence of various forms of malnutrition and associated factors among mother-child pairs residing in the same household. Methods A total sample of 2261 mother-child pairs from the Nepal Demographic and Health Survey (NDHS) 2016 were included in the study. Anthropometric measurements and hemoglobin levels of children and anthropometric measurements of their mothers were collected. Bivariate and multivariable logistic regression models were used to assess the factors associated with the double burden of malnutrition (DBM) and the triple burden of malnutrition (TBM). Results Prevalence of DBM and TBM was 6.60% (95% CI: 5.13-8.84) and 7.00% (95% CI: 5.42-8.99) respectively in the same households. In the adjusted multivariable logistic regression models, mothers with short stature (AOR = 4.18, 95% CI: 2.04-8.52), from the richest wealth quintile (AOR = 2.46, 95% CI: 1.17-5.15), aged over 35 years (AOR = 3.08, 95% CI: 1.20-7.86), and those who had achieved at least secondary level education (AOR = 2.05, 95% CI: 1.03-4.07) were more likely to suffer from the DBM. Similarly, mothers with short stature (AOR = 5.01, 95% CI: 2.45-10.24), from the richest wealth quintile (AOR = 2.66, 95% CI: 1.28-5.54), aged over 35 years (AOR = 3.41, 95% CI: 1.26-9.17), and those who had achieved at least secondary level education (AOR = 2.05, 95% CI: 1.00-4.18) were more likely to suffer from the TBM. Conclusions Overall, there is a low prevalence of double and triple burden of malnutrition among mother-child pairs in Nepal. Older mothers with short stature and those from richer wealth quintiles were more likely to suffer from double and triple burden of malnutrition.